Capability accumulation and product innovation: an agent-based perspective - Claudius Gräbner; Anna Hornykewycz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
The paper studies the relevance of product heterogeneity for innovation dynamics using an agent-based model. The vantage point is a short a review on the empirical relevance of capability accumulation for innovation processes and an assessment of how these processes are modelled theoretically in evolutionary micro and macroeconomic models. This shows that the macroeconomic literature so far has focused on process innovations. To facilitate the consideration of empirical and microeconomic insights on product innovation in macroeconomic models, a simple agent-based model, which may later serve as an innovation module in macroeconomic models, is introduced. Following up on recent empirical results, products in the model are heterogeneous in terms of their complexity and differ in their relatedness to each other. The model is used to study theoretical implications of different topological structures underlying product relatedness by conducting simulations with different 'product spaces'. The analysis suggests that the topological structure of the product space, the assumed relationship between product complexity and centrality as well as the relevance of product complexity in price setting dynamics have significant but nontrivial implications and deserve further attention in evolutionary macroeconomics. To this end, the model presented here may serve as a first step towards a module to be integrated in such a more comprehensive model framework.
Keywords: 330; Innovation; Produktentwicklung; Capability-Ansatz; Prinzipal-Agent-Theorie; Mikrofundierung; Produktgestaltung; Theorie